KANSA: high interoperability e-KTP decentralised database network using distributed hash table - Rolly Maulana Awangga; Nisa Hanum Harani; Muhammad Yusril Helmi Setyawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
e-KTP is an Indonesian Identity Card based on Near Field Communicator technology. This technology was embedded in every e-KTP card for every Indonesian citizen. Until this research, e-KTP technology never to be utilized by any stack-holder neither government agencies nor nongovernment organization or company. e-KTP Technology inside the card never been used and go with conventional with manual copy it with photocopy machine or take a photograph with it. This research was proposing an open standard to utilized e-KTP Technology. The open standard will bring e-KTP technology used as is and used broadly in many government agencies or much commercial company. This research was proposing decentralized network model especially for storing e-KTP data without breaking privacy law. Besides providing high specs of the server, a decentralized model can reduce the cost of server infrastructure. The model was proposing using Distributed Hast Table which was used for peer-to-peer networks. The decentralized model promised high availability and the more secure way to save and access the data. The result of this model can be implemented in many network topology or infrastructure also applicable to implement on Small Medium Enterprise Company.